An fMRI investigation of the effects of belief in free will on third-party punishment - Krueger, Frank (Oxford University Press, 2014)
The relationship between belief in free will (BFW) and third-party punishment (TPP) of criminal norm violations has been the subject of great debate among philosophers, criminologists and neuroscientists. We combined a TPP task with functional magnetic resonance imaging to investigate how lay people’s BFW might affect their punishment of hypothetical criminal offenses varying in affective content. Our results revealed that people with strong BFW punished more harshly than people with weak BFW, but only in low affective cases, likely driven by a more robust commitment to moral responsibility. This effect was mirrored by a stronger activation in the right temporo-parietal junction, a region presumably involved in attentional selection to salient stimuli and attribution of temporary intentions and beliefs of others. But, for high affective cases, the BFW-based behavioral and neural differences disappeared. Both groups similarly punished high affective cases and showed higher activation in the right insula. The right insula is typically activated during aversive interoceptive-emotional processing for extreme norm violations. Our results demonstrated that the impact of BFW on TPP is context-dependent; perhaps explaining in part why the philosophical debate between free will and determinism is so stubbornly persistent.